Religious Tolerance Education in Al Mukmin Islamic Boarding School of Ngruki - Taufik Nugroho; Siswanto Masruri; Ahmad Arifi (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to analyze religious tolerance education and the Islamic Religious Education curriculum containing religious tolerance at the Al Mukmin Islamic Boarding School (PPIM) of Ngruki. This research method uses a qualitative approach. While the data collection method used the method of documentation, participant observation, and in-depth interviews. The data were analyzed with a content analysis approach. This study found that PPIM Ngruki implemented religious tolerance education through two approaches, namely 1) integration of subjects, and 2) integration of learning outside the classroom. Religious tolerance material is integrated into subjects, namely Al-Qur’an Hadith, Akidah Akhlak, Fiqh, and History of Islamic Culture. Furthermore, religious tolerance material is taught outside the classroom through a program prepared by the Care Unit and Imaratu Syu’unit Thalabah (IST). The materials taught include tolerance, deliberation, neighborly etiquette, worship practices, and local culture, ukhuwah Islamiyah, and moral education. By teaching religious tolerance, students are embedded in an attitude of religious inclusiveness, having a view of equality and non-discrimination, understanding, and forming a religious Islamic boarding school environment. Thus, religious tolerance education implemented at PPIM Ngruki is part of the pesantren’s strategy to break some people’s negative stigma of being an intolerant pesantren. This study also shifted from a conservative orientation to an innovative moderate orientation.